Exploring Research Idea Growth with Litmap: Visualizing Literature Review Graphically - Dwi Sulisworo (Bincang Sains dan Teknologi, 2023)
This study presents a method for tracking the growth of research studies in a particular field or topic using a graphical representation of literature review with the help of Libmap. The step-by-step method involves selecting an article or a set of articles that represent the topic of interest and using Libmap to analyze and visualize the relationships between different concepts and ideas. The study starts with the article entitled "The role of mobile learning on the learning environment shifting at high school in Indonesia" written by Sulisworo et al. Libmap serves as a valuable tool for researchers during the process of writing scientific articles, as it allows for visual mapping and tracking of the development of research articles, identification of key articles or authors, exploration of citation patterns and influences, and contextualization of research within the existing literature. The visual representation provided by Libmap can also aid in identifying significant citations, highlighting influential articles, and identifying potential areas for further research. Overall, Libmap can enhance the literature review process, improve the quality of scientific articles, and contribute to the advancement of knowledge in various fields.